Efficacy of Digital Pricing Strategies on Customer Buying Decisions in the E-Commerce Industry: A PLS-SEM Approach - Abdulsalam, Tajudeen Alaburo; Omolaja, Remilekun Akimot; Tajudeen, Rofiat Bolanle; Abdulazeez, Sodiq Olamilekan (African Journal of Stability and Development (AJSD), 2024)
E-commerce is a vital component of global retail sustainability, expanding at a rate of 14% annually, fuelled by increased internet adoption (55%), with over five billion users worldwide. In Africa, e-commerce revenues have surged to $31.18 million, with Nigeria’s Business to Consumer (B2C) index hitting 53.2 points and boasting a 55% internet penetration rate in 2023, ranking fourth highest on the continent. The globalisation of markets has exposed ecommerce companies to economic downturns, compelling them to adopt strategic pricing approaches to ensure sustained profitability and competitiveness. Consumers have become more price-sensitive, emphasising the need for firms to accurately gauge pricing sensitivity to influence purchasing decisions effectively. This research explores how ecommerce stores utilise digital pricing strategies to impact the purchasing behaviour of Gen Z consumers in Nigeria. By employing an exploratory research design, the study utilised an online survey distributed through Google Form, targeting tech-savvy Gen Z consumers, who represent over 85% of the 384-sample size derived using the Borden sampling model. By being guided by the theory of planned behaviour, the PLS-SEM model indicates that special event pricing (0.433, 91.8% effect), sample product pricing (0.236, 85.0% effect), and loss leader pricing (0.236, 93% effect) significantly impact Gen Z’s consumer patronage (62.4%). Furthermore, product lining pricing (0.457, 93.7% high effect), captive pricing (0.161, 96.21% high effect), and optional pricing strategy (0.252, 96.0% medium effect) influence Gen Z’s online purchase satisfaction (67.2%). This underscores the importance of digital pricing strategies in shaping Gen Z’s online purchase behaviour. The research recommends the need for online stores to incorporate promotional and product mix strategies in business tactics; governments should monitor fair pricing practices, and online retailers should educate consumers about pricing strategies to foster informed purchasing decisions. The research acknowledges potential biases in data collection, stemming from unequal online access among Gen Z consumers, resulting in a partial representation of the diverse range of Gen Z behaviours across the continent, as various cultural, economic, and social factors can influence purchasing behaviours.